Transfer Spending in the English Premier League: The Haves and the Have Nots. (May 2015) - Burdekin, Richard C.K.; Franklin, Michael
Transfer spending among English Premier League clubs has increased drastically since the inception of the league, often funded by extremely wealthy owners who began purchasing majority stakes in clubs. Using data from the Deloitte Annual Review of Football Finance, we allow for different tiers of football clubs representing the haves and the have nots as well as a comparison between the first and second decades of the Premier League. Our finding that heightened spending has improved on-field performance only at the expense of hurting profitability is in line with win maximisation surmounting profit maximisation in today's Premier League.